Ingredients Recipe Application - Talib, Siti NurFaridah; Rashid, Zuraidah; Norsaidi, Nur Iman Sofia; MD Yasin, Mohd Suhaimi (Multidisciplinary Applied Research and Innovation, 2022)
An Ingredients Recipe Application is a mobile application that list out the recipe based, and suggests recipes for cooking simple recipes to users. Nowadays, with the existence of telecommunication devices, mobile devices and The Internet, it is easier for the public to find information on the internet. The application is developed to help users find and view different food recipes based on different categories. Other than displaying the picture of the food, name of the food, and list of ingredients needed and the tutorial to make it, this application also have the Youtube video link to serve the users more guide about the recipes. The methodology used in the development is ADDIE model which include analysis requirement, observation, design, testing and evaluation. In terms of time, this application provides a way that can help parents who are busy because of work as this application ingredients and categories used are simple and easily. Given the current situation of pandemic Covid-19, more people will stay at home and even work from home. More people spent their time at home and given this opportunity, this application aims to give easy guides and recipes ofor daily lives for the community. In conclusion, this application is hoped to one of the way to ease parents, students and the community who are new to this field of cuisine or willing to try another cuisine.